Elaine Steinbeck standing and talking with an unidentified man and woman. - unknown:::creator:::::::::::: (USA; Sag Harbor, New York, 2022)
Elaine Steinbeck standing and talking with an unidentified man and woman, possible at the the Old Whalers' Festival. Steinbeck helped establish Harborfest in 1964. It is also called the Old Whalers' Festival and The Sag Harborfest. Original is in safe.